Actors' roles in interaction and innovation in local systems: a conceptual taxonomy. Issue 3 (1st May 2015) - Guercini, Simone; Runfola, Andrea
Abstract : Purpose: – This paper aims to study the role of the focal firm in local communities. In particular, it aims at analyzing such firms' contribution to innovation, proposing a classification of the interactions and role systems that contribute to determining the innovational impact of focal firms. Design/methodology/approach: – This paper presents a concept-based study. The paper starts with a review of the literature to frame the concepts of local network and focal firm. Two key concepts, related to that of interaction, are then discussed: teaching and learning. Findings: – The paper proposes a taxonomy of the interactions and the roles systems that the focal firm can establish. The status of focal actor for innovation in a network stems, not from an "a priori" central strategic role on which the actor builds its interactions, but "a posteriori", from the actor's previously recognized roles in interactions on which network innovation is based. The local system may or may not be present in the interaction set of the business network. The interactions and roles systems define the type of local system. Research limitations/implications: – Research implications regard three main aspects: the different roles in the interactions; the types of actors in the local system; and the types of local systems involved in the processes of innovation. Originality/value: – The paper furnishes an original interpretation by focusing on focal firms as leaders in the innovation process, in the attempt to reconcile the "macro" perspective of local systems with the "micro" perspective of the individual firm.